2012
DOI: 10.1890/11-0381.1
|View full text |Cite
|
Sign up to set email alerts
|

Floodplain restoration enhances denitrification and reach‐scale nitrogen removal in an agricultural stream

Abstract: Abstract. Streams of the agricultural Midwest, USA, export large quantities of nitrogen, which impairs downstream water quality, most notably in the Gulf of Mexico. The two-stage ditch is a novel restoration practice, in which floodplains are constructed alongside channelized ditches. During high flows, water flows across the floodplains, increasing benthic surface area and stream water residence time, as well as the potential for nitrogen removal via denitrification. To determine two-stage ditch nitrogen remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
144
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(154 citation statements)
references
References 81 publications
8
144
2
Order By: Relevance
“…After decades of trying to quickly move runoff away from urban landscapes, perceptions regarding managing urban runoff have changed. There can be important water quality and flood safety benefits associated with reducing the velocity of runoff and retaining water on the landscape [56].…”
Section: Stream Impairment In Human Dominated Watershedsmentioning
confidence: 99%
“…After decades of trying to quickly move runoff away from urban landscapes, perceptions regarding managing urban runoff have changed. There can be important water quality and flood safety benefits associated with reducing the velocity of runoff and retaining water on the landscape [56].…”
Section: Stream Impairment In Human Dominated Watershedsmentioning
confidence: 99%
“…Proponents suggest the two-stage design should be self-maintaining in terms of sediment storage and transport. The vegetated bench provides an environment for enhanced biodiversity, nutrient uptake, and denitrification (Roley et al 2012). Sites suited to the practice can potentially be mapped based on bank height, which can be mapped using LiDAR.…”
Section: Example Applicationmentioning
confidence: 99%
“…Retaining vegetated benches increases the surface area of ditches and retention time during high flows. In Ohio and Indiana, denitrification rates have been found to be greater in sediments on naturally formed ditch benches than in sediments from side slopes of maintained trapezoidal ditches (Powell and Bouchard 2010), and having benches may influence in-stream denitrification rates (Roley et al 2012a(Roley et al , 2012b. Managing flow regimes in ditches can reduce N and moderate downstream P losses through greater capacity for sorption Strock et al 2007Strock et al , 2010Smith 2009).…”
Section: Figurementioning
confidence: 99%
“…A simulation study found that if 1% of a watershed was converted to benches within ditches, the increased storage could remove up to 20% of NO 3 -N loading in the system (Kallio 2010). There is extensive research on quantifying N removal rates and sediment dynamics in several ditches in Indiana, Michigan, and Ohio (Roley et al 2012a(Roley et al , 2012bRoley et al 2014;Davis et al 2015). At a constructed two-stage ditch in the Tippecanoe River watershed in Indiana, monitoring began one year prior to two-stage construction in both an upstream control and a downstream treatment reach and has continued for several years postconstruction.…”
Section: Figurementioning
confidence: 99%